2023
DOI: 10.3390/nu15184045
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Agricultural Systems in Teaching Kitchens: An Integrative Review and Thoughts for the Future

Alexis Cole,
Jennifer Pethan,
Jason Evans

Abstract: Diet-related chronic disease is a public health epidemic in the United States. Concurrently, conventional agricultural and food production methods deplete the nutritional content of many foods, sever connections between people and the origin of their food, and play a significant role in climate change. Paradoxically, despite an abundance of available food in the US, many households are unable to afford or attain a healthful diet. The linkages between agriculture, health, and nutrition are undeniable, yet conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Providing cooking education in combination with produce prescription can lead to increased consumption of fruits and vegetables leading to improved health outcomes [ 84 ]. Establishing teaching kitchens in partnership with agricultural agencies, community gardens, and farms would improve opportunities for networking and collaboration and serve the dual purpose of educating healthcare providers on the importance of nutrition, as well as a platform where cooking classes and demos can be provided to the community members and patients [ 85 - 87 ], thereby enhancing the long-term success of these initiatives.…”
Section: Challenges and Suggestionsmentioning
confidence: 99%
“…Providing cooking education in combination with produce prescription can lead to increased consumption of fruits and vegetables leading to improved health outcomes [ 84 ]. Establishing teaching kitchens in partnership with agricultural agencies, community gardens, and farms would improve opportunities for networking and collaboration and serve the dual purpose of educating healthcare providers on the importance of nutrition, as well as a platform where cooking classes and demos can be provided to the community members and patients [ 85 - 87 ], thereby enhancing the long-term success of these initiatives.…”
Section: Challenges and Suggestionsmentioning
confidence: 99%
“…Previous studies have indicated that these practices promote overall wellness and help prevent the development of NCDs such as heart disease, diabetes, and obesity [69,73]. Additionally, the deep connection to nature and the environment encourages a holistic approach to health, fostering a sense of harmony and balance within individuals and their communities [74]. In this regard, the reliance on traditional foods ensures that community members have access to nutrientdense and minimally processed options, which contribute to better overall health [69].…”
Section: Indigenous Games and Non-communicable Diseasesmentioning
confidence: 99%
“…For example, in indigenous communities, there may be initiatives that promote traditional farming practices and educate community members on the importance of consuming fresh fruits and vegetables. This not only increases access to nutrientdense foods but also helps preserve cultural traditions and knowledge [74]. Additionally, community-led physical activity programs such as group hikes or traditional dance classes can bring people together, promoting social connections while improving physical fitness [17].…”
Section: Indigenous Games and Non-communicable Diseasesmentioning
confidence: 99%
See 2 more Smart Citations